INTER-ETHNIC HARMONY AS A PROMISING DIRECTION FOR STRATEGIC PLANNING OF NATIONAL SECURITY POLICY IN THE RUSSIAN FEDERATION AT THE REGIONAL LEVEL (ON EXAMPLE OF REPUBLIC OF BURYATIA) - V. V. Goncharov; I. Z. Chimitova (Сравнительная политика, 2020)
The rapidly globalizing socio-political, state-legal and ﬁ nancial-economic development of national societies and states creates threats to ensure their national security. The crisis in international relations, which has deepened in recent decades, has given rise to new forms and methods of the inﬂ uence of the international community and the countries of the core of the world capitalist system on states that are opposed to the planned expansion of the dominant Western interpretations of the social structure. One of the effectively used areas of inﬂ uence on the state in order to undermine its national security are inter-ethnic, inter-religious and interracial relations. The results of such an impact on states with the goal of undermining its national security are: the growth and escalation of interethnic, interfaith and interracial conﬂ icts; the emergence of centrifugal trends in public administration; cultivation in society of fascist, Nazi, xenophobic, extremist ideological teachings; the implementation of large-scale internal migration of the population, undermining the stability of its economic development. Ensuring effective strategic planning of the national security policy in the Russian Federation requires the development and implementation of its new promising areas. As one of the promising areas of strategic planning of the national security policy in the Russian Federation at the regional level (using the example of the Republic of Buryatia), inter-ethnic harmony is provided. Under the interethnic consent in this study, using the positive experience of its provision in the Republic of Buryatia, the authors propose to designate the kind of interethnic tolerance inherent in some zones of long-term and good-neighborly interethnic contacts, characterized by the absolute predominance of non-conﬂ ict, complementary interactions between ethnic groups and their representatives over other forms of such interaction, as well as the general positive context of interethnic interaction. Its provision will require the implementation of a system of comprehensive measures at the federal and regional level, the purpose of which will be to create favorable conditions for the development of the country as a whole, as well as of the individual peoples inhabiting it, in the atmosphere of good-neighborly relations, positive interethnic, intercultural and inter-religious dialogue.